The Re-emergence of Diphtheria Amidst Multiple Outbreaks in Nigeria - Omosigho, Pius O.; John, Okesanya Olalekan; Adigun, Olaniyi Abideen; Hassan, Hakeem Kayode; Olabode, Olaleke Noah; Micheal, Abioye Sunday; Haruna, Usman Abubakar; Singh, Amandeep; Manirambona, Emery (Infectious Disorders - Drug Targets, 2024)
Diphtheria, a vaccine-preventable disease, has resurfaced in Nigeria, where many outbreaks have been reported in recent years. The outbreaks have occurred across the country, including in areas with high vaccination coverage. Corynebacterium diphtheriae, the causal agent, is a highly contagious bacteria that can cause severe respiratory and systemic symptoms and can be fatal if not treated. The reemergence of diphtheria in Nigeria is most likely due to a combination of factors, including gaps in routine immunization regimens. The outbreak is further aggravated by multiple epidemics, which have diverted resources and attention away from the emergency of other infectious diseases. Furthermore, there is a lack of awareness of diphtheria in Nigeria. With a focus on the difficulties in controlling the disease, methods of diagnosis, available treatments, and preventive measures, this study provides a thorough analysis of diphtheria, covering its historical context, clinical presentation, associated complications, and current outbreaks. It emphasizes how important vaccination, early detection, and better access to healthcare are in reducing diphtheria outbreaks. The study highlights the serious effects of diphtheria on public health, particularly in regions with scarce resources and vaccine resistance, and offers a number of suggestions to overcome these challenges and prevent further outbreaks.
Keywords: reemergence